Impact of off‐farm income on food expenditures in rural Bangladesh: an unconditional quantile regression approach - Mishra, Ashok K.; Mottaleb, Kh. A.; Mohanty, Samarendu (Wiley, 2015)
This study examines the effects of off‐farm income on food expenditures of rural Bangladeshi households. Our analysis yields unbiased estimates of the unconditional impact of off‐farm income on food expenditures and reveals the heterogeneous effects that occur across the distribution of total food consumption expenditures. The findings suggest that the impacts of off‐farm income are uniformly positive across the unconditional quantile regression and significantly increase food consumption expenditures for all quantiles, except for the 25th quantile. In addition, we found that schooling, experience, and location of the household increase the food expenditures of rural households. Most importantly, this article argues that female‐headed rural households in which the female works off the farm tend to have significantly lower food expenditures.